Komlos, John; Foundations of real-world economics. What every economic student needs to know - Colom Cabau, Agustí (Revista de Economía Crítica, 2024)
Reseña de: Komlos, John; FOUNDATIONS OF REAL WORLD ECONOMICS. WHAT EVERY ECONOMICS STUDENT NEEDS TO KNOW, Routledge, Nueva York – Londres, 3ª. Edición, 2023, (419 páginas) ISBN 978 1 032 00172 2